2016
DOI: 10.14744/nci.2016.52824
|View full text |Cite
|
Sign up to set email alerts
|

Is Triglyseride/ HDL Ratio A Reliable Screening Test for Assesment of Atherosclerotic Risk in Patients With Chronic Inflammatory Diseases?

Abstract: OBJECTIVE:The term chronic inflammatory disease (CID) refers to a category of inflammatory diseases that includes Ankylosing spondylitis (AS) and familial Mediterranean fever (FMF). The incidence of adverse cardiovascular events is greater among patients with CID, though they may not have conventional atherosclerotic risk factors. Endothelial dysfunction is one of the underlying fundamental mechanisms that trigger development of atherosclerotic alterations in arteries, and flow-mediated dilatation (FMD) is a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…We also observed these differences between FMF patients in the acute attack and those in attack-free period. Our findings are consistent with the results reported by Acay et al [14] and Keles et al [13]. However, we found no association of BsmI, FokI, and TaqI polymorphisms with serum lipids.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also observed these differences between FMF patients in the acute attack and those in attack-free period. Our findings are consistent with the results reported by Acay et al [14] and Keles et al [13]. However, we found no association of BsmI, FokI, and TaqI polymorphisms with serum lipids.…”
Section: Discussionsupporting
confidence: 93%
“…Another study showed that FMF patients had lower concentrations of total cholesterol and HDL-C compared to controls [38]. In addition, higher triglyceride to HDL-C ratio was found in patients with chronic inflammatory diseases, including FMF [13]. In this study, higher triglyceride and lower HDL-C concentrations were observed in FMF patients compared to control group.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The serum triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio, known as atherogenic index of plasma, is one of the major risk factors for CVD and metabolic syndrome (6). Higher TG/HDL C ratio has been associated with the presence of endothelial dysfunction (7). Furthermore, TG/HDL-C ratio has been proposed as a marker of insulin resistance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to explore the pathogenesis of atherosclerosis (AS) and search effective therapeutic methods. At present, the specific mechanism of AS remains unclear, and most scholars regard it as a chronic inflammatory response (4)(5)(6). Mononuclear macrophages have the most significant role in formation of atherosclerotic plaques, and the germinal cells of the innate immune system, which exist in each stage of atherosclerotic lesions (7,8).…”
Section: Introductionmentioning
confidence: 99%